EEG Characteristics and Anxiety Levels in Subjects with Different Levels of Success in Recovering Psychomotor Activity on Waking During Daytime Sleep - Cheremushkin, E. A.; Petrenko, N. E.; Dorokhov, V. B. (Neuroscience and behavioral physiology, 2022)
Studies in healthy adult volunteers with different levels of anxiety addressed the effectiveness of recovery of monotonous activity after brief episodes of daytime sleep. A continuous-discrete psychomotor test was used in which the experimental participants carried out two sequentially alternating tasks: counting to themselves from 1 to 10, accompanied by synchronous pressing of a button with the right hand, and counting to themselves without button-pressing. Subjects’ eyes were closed during the whole experiment. All subjects performed the test correctly before going to sleep. Subjects who started to make errors in the number of button presses and performed the test significantly more slowly after waking showed increases in the spectral power of EEG δ, θ, and α oscillations. These results point to marked signs of sleep inertia in the conditions in which the activity was performed. After waking, groups of subjects performing the task accurately in both experimental situations displayed no changes in the δ, θ, or α1 ranges compared with the beginning of the experiment. This fact, as well as the observation that test performance speed decreased slightly, provides grounds for suggesting that the sequelae of short-term sleep had smaller effects on performance of the psychomotor test in these subjects. We suggest that the decrease in α2 power in the caudal EEG leads reflects activatory processes supporting more effective activity in these conditions. Short-lived daytime sleep had different effects on the effectiveness of recovery of activity in healthy subjects with different anxiety levels. After waking, subjects with elevated anxiety showed greater signs of sleep inertia and performed the psychomotor test task worse than at the beginning of the experiment before going to sleep. The effect of short-term sleep on the effectiveness of test performance was significantly less marked in less anxious subjects.